Stable isotopes and carbon and nitrogen ratio of hyperiid amphipod in the Southeast Pacific - Espinosa-Leal, Liliana (PANGAEA, 2019)
Carbon and nitrogen value for hyperiid amphipods in the Southeast Pacific.
Keywords: Abundance; community; hyperiid amphipod; Southeast Pacific